Effectiveness of Ship Sinking of Illegal Fishing in Term of the Improvement of Local Fishermen Income - Maskur, Muhammad Azil; Masyhar, Ali; Kusuma, Bagus Hendradi; Widyawati, Anis (Universitas Negeri Semarang (UNNES), 2021)
Illegal fishing in Indonesia is at an alarming point, that the Ministry of Maritime Affairs and Fisheries made a policy of ship sinking. There are pros and cons related to these sanctions, not even a little resistance from both the internal government itself and the mafia who have been enjoying the results of Illegal Fishing. The sustainability of this policy has been almost 4 years. Data represents that through this policy, illegal fishing has dropped dramatically, so that when viewed in terms of criminal penalties for deterrence (absolute theory), the policy is very effective. However, whether the policy has an impact on the income of local fishermen, logically, when there is illegal fishing of small fish, the income of local fishermen increases. In order to figure out the effectiveness of illegal fishing sanctions in relation to increasing local fishermen’s income, the researchers determined the location of the study in the Tambak Lorok Fishing Village in Semarang.